Towards an Organizational Model Based on the Human Being Seen as an Allopoietic Gray Box Information Processor - Tarride-Fernandez, M (Emerald Publishing, 2024)
Purpose: The paper aims to contribute conceptually to the conversation about organizational models and to the future development of an organizational diagnostic method, based on the human being seen as an allopoietic information processing gray box. Design/methodology/approach: Methodologically, the approach is qualitative and interpretative, using the concepts of autopoiesis and allopoiesis of H. Maturana and F. Varela, the ideas of cybernetic machine, black box and functional homomorphism of W.R. Ashby, moving from the human being to the organizations producing goods and/or services. Findings: Observing the human being as an allopoietic gray box allowed us to confirm the human being as an information-producing entity and the nervous system as its productive component. The functions distinguished were to emote, feel, perceive, think, memorize, decide, communicate, regulate, control, coordinate and move. Similarly, the proposed organizational model is composed of the same functions in which emoting is homologated with distributed leadership for the achievement of the organizational climate and to move with production. Notwithstanding the circularity of affectation between the functional components, the climate is the basis of organizational operation and consequently, the decisional closure distributed between owners and employees. Research limitations/implications: This is a theoretical proposal that needs to be discussed, and although there are precedents that could help in this regard, it is essential to enrich the model and derive thereof specific tools that can be applied. Practical implications: A general model is provided from which methods of organizational design, diagnosis and treatment could be derived. Social implications: The proposed model is expected to be a contribution to organizational research discussion. Originality/value: It is considered that the work has a certain degree of originality when proposing a functional organizational model of a general nature, based on the emotionality of the people that constitute it. © 2023, Emerald Publishing Limited.